Natural Resources and Violent Conflict: Resource Abundance, Dependence and the Onset of Civil Wars - Christa N. Brunnschweiler; Erwin Bulte (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
In this paper we examine the claim that natural resources invite civil conflict, and challenge the main stylized facts in this literature. We find that the nature of causation between resource dependence and civil war is opposite to conventional wisdom. In particular, (i) civil war creates dependence on primary sector exports, but the reverse is not true, and (ii) resource abundance is associated with a reduced probability of the onset of war. These results are robust to a range of specifications and, considering the conflict channel, we conclude there is no reason to regard resources as a general curse to development.
Keywords: Q34; O11; N40; N50; 330; Civil war; resource abundance; resource dependence; greed versus grievance; resource curse; Bürgerkrieg; Rohstoffvorkommen; Kausalanalyse; Welt